Метод сортировки относительных позиций синхроимпульсов по частоте их появления - Кичак, В.М.; Тромсюк, В.Д. (Проблемы управления и информатики, 2016)
Запропоновано метод сортування відносних позицій синхроімпульсів за частотою їх появи, що необхідно для знаходження істотної відносної позиції синхросимвола. Запропонований метод дозволяє здійснювати сортування елементів черги. The problem of sorting the relative positions of the synchroimpulses by frequency of their occurrence, is considered the solution of which is necessary for finding of substantial relative position synchrosymbols. The proposed method allows one to sort items in the queue each time only on the basis of input and output elements of the queue.